2008
DOI: 10.1093/rpd/ncn147
|View full text |Cite
|
Sign up to set email alerts
|

A pixel detector-based single photon-counting system as fast spectrometer for diagnostic x-ray beams

Abstract: Recent advances in semiconductor pixel detectors and read-out electronics allowed to build the first prototypes of single photon-counting imaging systems that represent the last frontier of digital radiography. Among the advantages with respect to commercially available digital imaging systems, there are direct conversion of photon energy into electrical charge and the effective rejection of electronic noise by means of a thresholding process. These features allow the photon-counting systems to achieve high im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Counting only events above a given energy threshold will minimise the contribution of detector and electronic noise, providing a higher detective quantum efficiency (DQE) compared to other direct radiography techniques [12]. Another possible application for such a system, as a fast spectrometer to study the energy spectrum of diagnostic beams produced by X-ray tubes, has been reported [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Counting only events above a given energy threshold will minimise the contribution of detector and electronic noise, providing a higher detective quantum efficiency (DQE) compared to other direct radiography techniques [12]. Another possible application for such a system, as a fast spectrometer to study the energy spectrum of diagnostic beams produced by X-ray tubes, has been reported [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…When equipped with multithresholding circuits, these systems enable energyresolving photon-counting (EPC) imaging where the deposited energy from each interacting x-ray photon is estimated. [1][2][3][4][5][6][7] It is anticipated that the resulting spectral distribution of energy-depositing events will lead to advanced spectroscopic procedures [8][9][10][11][12][13][14] and improve image quality by reducing image noise from random physical processes including Swank and electronic readout noise. 7,15 While photon-counting methods are receiving a great deal of interest, there remain many challenges to overcome.…”
Section: Introductionmentioning
confidence: 99%